Colonization, spread and persistence of Salmonella (Typhimurium, Infantis and Reading) in internal organs of broilers - Jinquan Wang; Davis A. Fenster; Sasikala Vaddu; Sujitha Bhumanapalli; Jasmine Kataria; Gaganpreet Sidhu; Cortney Leone; Manpreet Singh; Rami A. Dalloul; Harshavardhan Thippareddi (Poultry Science, 2024)
ABSTRACT: Transfer of Salmonella to internal organs of broilers over a 35 d grow-out period was evaluated. A total of 360 one-day old chicks were placed in 18 floor pens of 3 groups with 6 replicate pens each. On d 0, broilers were orally challenged with a cocktail of Salmonella (equal population of marked serovars; nalidixic acid-resistant S. Typhimurium, rifampicin-resistant S. Infantis, and kanamycin-resistant S. Reading) to have 3 groups: L (low; ∼2 log CFU/bird); M (medium; ∼5 log CFU/bird); and H (High; ∼8 log CFU/bird). On d 2, 7 and 35, 4 birds/pen were euthanized and ceca, liver, and spleen samples were collected aseptically. Gizzard samples (4/pen) were collected on d 35. The concentration of Salmonella in liver and spleen were transformed to binary outcomes (positive and negative) and fitted in glm function of R using cecal Salmonella concentrations (log CFU/g) and inoculation doses (L, M, and H) as inputs. On d 2, H group showed greater (P ≤ 0.05) cecal colonization of all 3 serovars compared to L and M groups. However, M group showed greater (P ≤ 0.05) colonization of all 3 serovars in the liver and spleen compared to L group. Salmonella colonization increased linearly in the ceca and quadratically in the liver and spleen with increasing challenge dose (P ≤ 0.05). On d 35, L group had greater (P ≤ 0.05) S. Infantis colonization in the ceca and liver compared to M and H groups (P ≤ 0.05). Moreover, within each group on d 35, the concentration of S. Reading was greater than those of S. Typhimurium and S. Infantis for all 3 doses in the ceca and high dose in the liver and gizzard (P ≤ 0.05). Salmonella colonization diminished in the ceca, liver, and spleen during grow-out from d 0 to d 35 (P ≤ 0.05). On d 35, birds challenged with different doses of Salmonella cocktail showed a similar total Salmonella spp. population in the ceca (ca. 3.14 log CFU/g), liver (ca. 0.54 log CFU/g), spleen (ca. 0.31 log CFU/g), and gizzard (ca. 0.42 log CFU/g). Estimates from the fitted logistic model showed that one log CFU/g increase in cecal Salmonella concentration will result in an increase in relative risk of liver and spleen being Salmonella-positive by 4.02 and 3.40 times (P ≤ 0.01), respectively. Broilers from H or M group had a lower risk (28 and 23%) of being Salmonella-positive in the liver compared to the L group when the cecal Salmonella concentration is the same (P ≤ 0.05). Oral challenge of broilers with Salmonella spp. with various doses resulted in linear or quadratic increases in Salmonella colonization in the internal organs during early age and these populations decreased during grow-out (d 35). This research can provide guidance on practices to effectively mitigate the risk of Salmonella from chicken parts and enhance public health.